OBSERVATIONAL STUDY OF SHAWASA KASHTATA LAKSHAN PARIKSHAN IN MEDOVRIDDHI INDIVIDUAL WITH SPECIAL REFERENCE TO VITAL CAPACITY (International Journal of Food and Nutritional Sciences, 2022)
the equilibrium of various structural and functional units of the body, including Dosha, Dhatu, Mala, Agni, and Indriya, to promote well-being. Imbalances in these units can lead to diseases. The functioning of the body is governed by the three Doshas, which control the seven bodily tissues (Rasa, Rakta, Mamsa, Meda, Asthi, Majja, and Shukra) and ensure its continuous operation. Waste products generated during daily activities are referred to as Malas, and our daily life activities depend on this functioning.The definition of a healthy body, according to Sushruta, is crucial for achieving the ultimate goal among the Chaturvidha Purushartha. Sushruta considers "Madhyam Sharira" (moderate body) as the best, while "Atisthula" (excessive weight) or "Ati krusha" (excessive thinness) is associated with complaints. Charak and Vagbhat, on the other hand, believe that a lean body ("krusha sharir") is ideal. Charak also highlights eight impediments known as "Nindita purusha."